Stanazolol--an anabolic steroid that does not influence parathyroid hormone response to hypercalcemia in postmenopausal women - Zofková, I; Röjdmark, S; Kancheva, R L (Calcified tissue international, 1994)
Estrogen influences the calcium-induced suppressibility of parathyroid hormone (PTH) in postmenopausal women. We tested the hypothesis that parathyroid gland function is also sensitive to the anabolic steroid, stanazolol. The calcium-induced suppressibility of PTH was investigated in 11 osteoporotic postmenopausal women on two occasions, before and after 1 month's oral treatment with stanazolol. Compliance to treatment was checked by the determination of serum luteinizing hormone (LH) and testosterone. Serum intact PTH and ionized calcium were estimated before and 5, 60, and 120 minutes after I.V. calcium load. Calcium-induced PTH suppression was of a similar magnitude before and after stanazolol, although calcium increments were identical. The results imply that stanazolol--at biologically effective doses--does not affect PTH responsiveness to hypercalcemia in postmenopausal women.
Keywords: Parathyroid Hormone; anabolika; Calcium; Time Factors; lidé středního věku; stanozolol; Testosterone; radioimunoanalýza; Dose-Response Relationship, Drug; časové faktory; estrogeny; luteinizační hormon; Luteinizing Hormone; vztah mezi dávkou a účinkem léčiva; Humans; testosteron; Middle Aged; aplikace orální; Anabolic Agents; Female; Stanozolol; postmenopauzální osteoporóza; hyperkalcemie; Administration, Oral; ženské pohlaví; postmenopauza; vápník; parathormon; Hypercalcemia; Estrogens; Radioimmunoassay; lidé; Postmenopause; Osteoporosis, Postmenopausal